Targeting Pseudomonas aeruginosa biofilm with an evolutionary trained bacteriophage cocktail exploiting phage resistance trade-offs - Kunisch, Fabian; Campobasso, Claudia; Wagemans, Jeroen; Yildirim, Selma; Chan, Benjamin K.; Schaudinn, Christoph; Lavigne, Rob; Turner, Paul E.; Raschke, Michael J.; Trampuz, Andrej; Gonzalez Moreno, Mercedes (Nature communications, 2024)
Spread of multidrug-resistant Pseudomonas aeruginosa strains threatens to render currently available antibiotics obsolete, with limited prospects for the development of new antibiotics. Lytic bacteriophages, the viruses of bacteria, represent a path to combat this threat. In vitro-directed evolution is traditionally applied to expand the bacteriophage host range or increase bacterial suppression in planktonic cultures. However, while up to 80% of human microbial infections are biofilm-associated, research towards targeted improvement of bacteriophages’ ability to combat biofilms remains scarce. This study aims at an in vitro biofilm evolution assay to improve multiple bacteriophage parameters in parallel and the optimisation of bacteriophage cocktail design by exploiting a bacterial bacteriophage resistance trade-off. The evolved bacteriophages show an expanded host spectrum, improved antimicrobial efficacy and enhanced antibiofilm performance, as assessed by isothermal microcalorimetry and quantitative polymerase chain reaction, respectively. Our two-phage cocktail reveals further improved antimicrobial efficacy without incurring dual-bacteriophage-resistance in treated bacteria. We anticipate this assay will allow a better understanding of phenotypic-genomic relationships in bacteriophages and enable the training of bacteriophages against other desired pathogens. This, in turn, will strengthen bacteriophage therapy as a treatment adjunct to improve clinical outcomes of multidrug-resistant bacterial infections. Using a biofilm evolution assay, this study improves the antimicrobial and antibiofilm efficacy of Pseudomonas aeruginosa bacteriophages, while a two-phage cocktail shows further improved antimicrobial efficacy without incurring dual-bacteriophage-resistance.